Household expenses in healthcare and its coping mechanism in rural Nepal - Shrestha, Aliza; Nepal, Susmita; Poudyal, Aassmi (International Journal Of Community Medicine And Public Health, 2021)
Background: In Nepal, the most frequent mode of payment for health care is household expenditure. It accounts for more than half of all health-care expenditures. In addition, the study intends to investigate household expenditure on health care and its coping mechanisms in Nepal’s rural districts. Methods: This is a quantitative, cross-sectional study in which 410 households were chosen using a multiple sampling procedure. The research study region was chosen using a purposive sampling strategy. The two wards for the study were chosen by a lottery system. The estimated households were then chosen using a systematic random selection technique. A semi-structured questionnaire was utilized to gather data, and a face-to-face interview with the household head was undertaken to obtain the data. SPSS version 20 was used to analyze all of the data. Results: The overall household health expenditure in Miklajung rural municipality was determined to be 31.7% in the previous six months, with the biggest expenditure in medicine/drugs or pharmacies, followed by in-patient care and health treatment abroad. Income/savings was discovered to be a major coping mechanism used to deal with household expenditure and was found to be significantly associated in a bivariate analysis with type of illness, age, and more with a confidence interval of 95% in a bivariate analysis. Conclusions: At the conclusion of the investigation, we discovered that people spent the most money on medicines and drugs, followed by in-patient hospital care. According to the findings, a significant portion of the target group used their income and savings to cover unexpected healthcare costs.